2016
DOI: 10.1017/s0007485316000080
|View full text |Cite
|
Sign up to set email alerts
|

Slow and fast development in two aphidophagous ladybirds on scarce and abundant prey supply

Abstract: Developmental rates are highly variable, both within and between genotypes and populations. But the rationale for two differential (slow and fast) developmental rates within same cohort under varying prey supply has yet not been explored. For this purpose, we investigated the effect of scarce and abundant prey supply on slow and fast development at 27°C in two aphidophagous ladybirds, Menochilus sexmaculatus (Fabricius) and Propylea dissecta (Mulsant) and its effect on their body mass and reproductive attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…Omkar and Pervez (2003) also reported that the pre-oviposition period of female Propylea disecta increased with increase in the duration of prey deprivation. The finding agrees with the optimal foraging theory, which states that females desist from laying eggs in habitats that cannot support progeny survival (Kindlmann & Dixon 1993, Singh et al 2016.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Omkar and Pervez (2003) also reported that the pre-oviposition period of female Propylea disecta increased with increase in the duration of prey deprivation. The finding agrees with the optimal foraging theory, which states that females desist from laying eggs in habitats that cannot support progeny survival (Kindlmann & Dixon 1993, Singh et al 2016.…”
Section: Discussionsupporting
confidence: 87%
“…The development of offspring is influenced by both the nutrient reserve in eggs and the food provided to them during development (Singh et al 2019(Singh et al , 2020. Prey deprivation severely affects the development and survival of ladybirds (Omkar & Pervez 2003, Singh et al 2016. It is believed that under prey scarce conditions, the energy resources are utilized to maximize the survival and reproduction (Legaspi & Legaspi 1998).…”
Section: Introductionmentioning
confidence: 99%
“…According to this, tradeoffs that imply competing allocations between current versus future reproduction might respond to a universal logic and might ubiquitously conform a fast–slow continuum ( Figueredo et al, 2005 ; Del Giudice, 2020 ). In support of this, evidence of variation along a fast–slow axis within single species has been reported across resource gradients ( Singh et al, 2016 ; Tabak et al, 2018 ).…”
Section: Introductionmentioning
confidence: 65%
“…In this trial, 92% of S. interruptus larvae were able to complete development, approximately half of the H. variegata larvae reached adulthood, whereas only one out of 14 A. bipunctata managed to do so. Various fitness components, such as oviposition rate, longevity, or searching capacity might be seriously compromised when prey supply during larval development is limited (Singh et al., ). These results may be of interest from an applied point of view in terms of aphid biological control.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, the use of alternative ladybird species should be considered. Although counterintuitive, less voracious species could present a better options if they are capable of completing their development with fewer prey and thus establish in the crop (Singh et al., ). Such species could actually have potential to be used in a preventative aphid control strategy, thereby reducing the cost to the grower.…”
Section: Introductionmentioning
confidence: 99%